Quality Analysis of Motion and Force Science Test Items Using TAP: Analisis Kualitas Item Uji Sains Gerak dan Gaya Menggunakan TAP - Salma Ramadhina Fatahillah; Nur Efendi (Academia Open, 2025)
General Background: In the era of Industry 4.0, educational assessment must align with 21st-century competencies, requiring high-quality test instruments capable of measuring students’ cognitive abilities accurately. Specific Background: The quality of multiple-choice items is determined by parameters such as validity, reliability, difficulty level, discriminating power, distractor effectiveness, and cognitive level distribution according to Bloom’s Taxonomy. Knowledge Gap: In practice, many school examinations are developed from existing question banks without systematic quantitative analysis, resulting in instruments that may not fully represent students’ competencies or higher-order thinking skills. Aims: This study aimed to analyze the quality of Grade VII science test items on Motion and Force using the Test Analysis Program (TAP) based on standard psychometric criteria and cognitive domains. Results: Analysis of 40 items from 52 students indicated that 95% of the items were valid, with very high reliability (KR-20 = 0.929; split-half = 0.925). The difficulty level was dominated by easy items (82.5%), most items showed high discriminating power (60%), and 90% of distractors functioned effectively. The cognitive distribution was concentrated at the analyzing level (C4), with very limited representation of higher levels. Novelty: The study integrates TAP-based statistical analysis with cognitive domain mapping to provide a comprehensive evaluation of science test quality. Implications: The findings suggest that while the instrument meets most quality standards, improvements are needed in difficulty balance and higher-order thinking coverage to support meaningful assessment in contemporary science education. Highlights: Most questions met statistical standards for psychometric soundness. Items were heavily concentrated in low-to-moderate challenge categories. Higher cognitive levels were minimally represented in the instrument. Keywords: Test Analysis Program; Science Assessment; Item Analysis; Motion And Force; Junior High School